Estudos das propriedades morfológicas e eletrônicas em: interfaces grafeno/metal e isolantes topológicos - Wendell Sim?es e Silva (2014)
This thesis presents the topological insulator Bi(1x)Sbx(110) ARPES results and the graphene growth on Pt(533) vicinal surface. The topological insulators support metallic surface states with closed Fermi contours encircling an odd number of Trims. So far, the experimental studies has had the focus centered, basically, at surfaces with only one Dirac point, nevertheless, three points are also expected for certain surfaces orientations of several topological insulators. Here, we are going to present the data of Bi(1x)Sbx(110) eletronic structure which has three Dirac points and was predicted by Teo et all [1], in contrast to closed-packed (111) of the same material that supports only one Dirac point. Using angle-resolve photoemission spectroscopy we observed the expected metallic surface states with closed contours around the Trims at the Fermi level of the Bi(1x)Sbx(110) confirming the prediction of the surface states topology. The vicinal surfaces are of great importance in the field of catalyses, due to: 1) its application to ammonia oxidation, 2) eletronics, due to electron confinement at the terraces created by potential barriers on the steps and 3) as a template to the growth of carbon compound molecules, such as C3H6 and graphene. The Pt(533) surface has the step and terrace orientations at (100) and (111) direction, respectively. This is very important because (111) surfaces tend to possess surface states at the Fermi level. This states are quite known for the platinum substracts. The experiments were performed in a chamber where the Pt(533) substrtate was subjected to a heat treatment at a temperature around 800C which induced the surface faceting in two well-defined direction, caused by the segregation of carbon to the surface. The same faceting pattern occurred when we submit the sample to a C3H6 atmosphere at the temperature of 650C, although the facets now have different directions. Morphological analysis of the clean surface and facets were performed using the low-energy electrons diffraction, LEED, and scanning tunneling microscopy, STM. The chemical analysis was performed by X-ray photoelectron spectroscopy, XPS. Our results for Pt (533) are similar to results found for the Ni(755) as presented in D. Usachovs paper. They show that the graphene growth on the substrate increases the surface tension of the outer surface causing it to faceting. Based on our experimental results and the reference [5], we performed theoretical calculations simulating the dynamics of electron diffraction of a 2% graphene expanded lattice. The results were quite consistent with the presence of graphene on the facets created on Pt (533).